Sistem Pencatatan Akuntansi Pengadaan Rutin Barang Dan Jasa Pada PT. PLN (Persero) Up 3 Banyuwangi - Devi Ayu Umami; Munir Is’adi (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Not just people attempt to address their issues for labor and products yet additionally organizations in light of the fact that satisfying these labor and products plays a significant part in supporting the organization's functional exercises. The point of securing labor and products is as a supporting element in completing exercises with the goal that they run well and get most extreme outcomes. On account of obtainment of merchandise/administrations, interior control should exist for each field in the work association in a task. Because the procurement procedure is susceptible to procedural inconsistencies, an element of internal control is required. Based on the description above, the author chose PT PLN (Persero) UP3 Banyuwangi as the basis for writing the journal Kiai Haji Achmad Siddiq Jember University, Faculty of Islamic Economics and Business entitled "ACCOUNTING RECORDING SYSTEM FOR ROUTINE PROCUREMENT OF GOODS AND SERVICES AT PT PLN (PERSERO) UP 3 BANYUWANGI ”